Model Pengukuran Kinerja Customer Relationship Management dalam Industri Perbankan - Freddy Simbolon (Bina Nusantara University, 2014)
High competition in the banking industry requires the banking industry to properly manage relationships with customers, as it is known as Customer Relationship Management (CRM). CRM applications will become effective when supported by information technology. Investment in information technology is not a small investment, because the higher the information technology, the greater the value of the investment. This study aims to obtain a model of CRM performance measurement in the banking industry efficiently and effective. The method in this study uses descriptive analytical method, while the results obtained in this study is a CRM Scorecard. CRM Scorecard is one of the approach models that correctly measure the performance of CRM, which is based on information technology. Through CRM Scorecard approach, information technology investment in CRM is no longer seen as a cost center, but seen to be a profit center, because the company can manage customers efficiently and effectively in order to enhance shareholder value in the future.